2013
DOI: 10.1002/ana.23967
|View full text |Cite
|
Sign up to set email alerts
|

miR‐155 as a multiple sclerosis–relevant regulator of myeloid cell polarization

Abstract: Our results demonstrate that miR-155 regulates proinflammatory responses in both blood-derived and central nervous system (CNS)-resident myeloid cells, in addition to impacting subsequent adaptive immune responses. Differential miRNA expression may therefore provide insight into mechanisms responsible for distinct phenotypic and functional properties of myeloid cells, thus impacting their ability to influence CNS injury and repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
159
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 199 publications
(169 citation statements)
references
References 48 publications
1
159
1
2
Order By: Relevance
“…In the brains of MS patients, microRNA expression is significantly altered and has been suggested to significantly influence inflammation and repair capacity 35, 36. In astrocytes, both miR‐155 and miR‐146a are significantly upregulated in active MS lesions; laser‐captured astrocytes from MS lesions express miR‐155 in situ 35.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the brains of MS patients, microRNA expression is significantly altered and has been suggested to significantly influence inflammation and repair capacity 35, 36. In astrocytes, both miR‐155 and miR‐146a are significantly upregulated in active MS lesions; laser‐captured astrocytes from MS lesions express miR‐155 in situ 35.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the validated miR‐155 target SOCS138 is a potent regulator of astrocyte cytokine/chemokine secretion,39 suggesting that a miR‐155/SOCS1 axis could mediate the anti‐inflammatory effects of DMF. miR‐146a is an inflammation resolving microRNA whose expression is upregulated in CNS lesions and peripheral immune cells of MS patients 35, 36. As such, the reduced expression of miR‐146a in fumarate‐treated astrocytes suggests an MS‐relevant resolution of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…54 They suggested that these upregulated miRNAs in MS lesions suppress CD47 expression, which leads to enhanced phagocytosis of myelin by microglia/macrophages. 54 Abnormal upregulation of miR-155 in MS microglia was also reported by Moore et al 61 Because miRNA profiles differ substantially between cell populations, miRNA profiling in purified immune cell populations, rather than in total PBMC, is preferred in studies aiming to understand the biological significance of altered miRNA expression in MS (Table 3). 42 58 In particular, they emphasized that elevated expression of miR-92a-1* was seen only in RRMS patients, and the expression level correlated with disability and disease duration in these patients.…”
Section: Mirna In Msmentioning
confidence: 82%
“…L'utilisation de ces biopuces appliquée à différents tissus provenant de patients atteints de SEP a ainsi mis en évidence une altération de l'expression de nombreux miARN au cours de la maladie. La détection des miARN a été réalisée à partir de tissus (sang total [13,14], tissu nerveux [15,16], hippocampe [17]), de cellules (cellules mononucléées du sang [18][19][20], lymphocytes B [21][22][23] et T [11,20,[23][24][25][26], monocytes [27], microglie [27], cellules endothéliales [28,29]) ou de fluides extracellulaires (sérum/plasma [12,18,[30][31][32][33], LCR [34]). Nous répertorions de manière systématique dans cette revue, l'ensemble des données issues de la littérature concernant les miARN SYNTHÈSE REVUES miR-155 -/- [37]) sont résistantes à l'induction d'une EAE.…”
Section: Dérégulation Des Miarn Chez Les Patients Atteints De Sepunclassified
“…Cependant, le passage des vésicules issues de cellules immunitaires au travers de la barrière hémato-encé-phalique et leur capture par des cellules du SNC reste à démontrer. Il est également important de définir l'origine de la dérégulation de miR-155 et de comprendre comment elle s'étend à d'autres compartiments (sérum [12], cellules endothéliales [29], monocytes [27], microglie [27], tissu nerveux lésé [15]). …”
Section: Conclusion Et Perspectivesunclassified